Between Seeing and Reflecting: Child Suppression in Literacy Internship Reports - Cipullo, Tathiane Graziela (2020)
The purpose of this article is to discuss teacher training in order to work with children based on the analysis of internship reports. We assume, as a premise, that writing about professional practices is more than a simple means of documentation or proof of activities; rather, it is a moment of reflection and analyses of the practice which can result in the production of knowledge. We analyzed ten internship reports in order to verify how undergraduates establish a relation between theory and practice. Considering the results, we can note that the main purpose of pedagogic thought is suppressed in the reports; in other words, the child appears little, and, when it is described, it is mainly as a faulty being, one who has not learned, has not developed, does not do or does not meet adult expectations. These data lead us to question what is happening in the current pedagogical training courses and the reasons why studies do not reflect on their practices.